(untitled) (Revista de Medicina Clinica, 2025)
Background: Current food systems, while ensuring food availability, generate negative impacts on human health and the environment, including emissions, biodiversity loss and water stress. Global malnutrition - from obesity to micronutrient deficiencies - highlights the need to transform these systems towards sustainable, equitable and culturally relevant diets. The aim was to conduct a systematic review of the scientific literature that analyzes interventions, indicators and outcomes related to sustainable food, in order to identify their implications for global nutrition, evaluate their effectiveness in different socioeconomic contexts and propose guidelines for future evidence-based public policies. Methods: This systematic review analyzes how sustainable approaches in food systems influence population nutrition, integrating environmental, social and economic criteria. Through a rigorous search and methodological assessment with PRISMA, we selected studies linking sustainable dietary patterns with health indicators in various contexts. Results: The review followed PRISMA guidelines, ensuring methodological rigor in the selection of studies. A total of 349 records were identified in scientific databases, and after applying inclusion criteria focused on nutrition and SDGs, 9 randomized clinical trials were selected. These studies provide key evidence on health, food equity and sustainability. Conclusion: The studies reviewed show a comprehensive view of the link between nutrition and the SDGs, combining conceptual, empirical and strategic approaches.